THE INFLUENCE OF ANTIRETROVIRAL AND ANTITUBERCULOSIS AGENTS ON THE BIOCHEMICAL AND HISTOPATHOLOGICAL INDICES OF LIVER FUNCTION IN RATS - O. O. Shevchuk; K. A. Posokhova; O. M. Oleshchuk; T. V. Datsko (International Journal of Medicine and Medical Research, 2014)
Background. Standard antituberculosis treatment and highly active antiretroviral therapy are frequently associated with hepatotoxicity leading to drugs discontinuation. Objective. This study aimed to assess the signs of hepatotoxicity in albino rats in case of simultaneous usage of tuberculostatics (TBS) and antiretroviral agents (ART). Methods. Healthy rats were divided in 4 groups: 1st control group; 2nd group was given tuberculostatics (isoniazid – 50 mg/kg, rifampicin – 50 mg/kg and pyrazinamide – 1500 mg/kg); 3rd group was given ART (efavirenz – 150 mg/kg and stavudine – 5 mg/kg); 4th group was given TBS and ART. The animals were sacrificed painlessly on the 29th day; blood and liver samples were obtained. The main biochemical and histopathological indices were determined. Conclusions. Comparing with control group, repeated usage of TBS caused the prominent liver injury with cytolysis and cholestasis signs, decreasing of CYP3A and CYP2E1 isozymes activity and dysfunction of protein synthesis by the liver. ART (efavirenz and stavudine) caused the elevation of transaminases activity with the increase of serum bilirubin level at the background of increase in cytochrome 450 isoforms 3A and 2E1 activities and total serum protein. The antiretroviral agents in case of simultaneous administration with the antituberculosis drugs diminished the hepatotoxic effects of first-line drugs for tuberculosis treatment which was confirmed by the study of liver histopathology. Such results of our experimental study give encouragement for further detailed clinical research of drug-drug interaction of both pharmacological groups due to the rising cases of HIV-associated tuberculosis in the whole world.